Penerapan Metode Skimming Melalui Media Digital Glossary Dictionary (DGD) Untuk Meningkatkan Pemahaman Teks Naratif di MTsN 6 Bantul - Widayati, Ely (Allimna: Jurnal Pendidikan Profesi Guru, 2022)
The purpose of this article is to describe the extent of the application of the skimming method through the Digital Glossary Dictionary (DGD) in increasing the understanding of narrative texts in class IX B MTsN 6 Bantul odd semester of 2022/2023. The method used is Classroom Action Research (CAR). The results showed that the application of the skimming method through the use of the DGD digital dictionary proved a positive change. This is evidenced by the increase in several aspects, namely student activity, knowledge value, and positive responses from students. In the aspect of student activity, pre-cycle to cycle I activities increased by 11%. As for from cycle I to cycle II also experienced an increase of 3.53%. Likewise, the results of research on aspects of knowledge that are measured using multiple choice written tests. The results of cycle tests carried out at the end of the cycle showed an average increase in yield by 9%. The test results from cycle I to cycle II obtained an average value of 64.67 increasing to 80.6 or 11%. Aspects of student achievement in terms of English subject matter of narrative text material in pre-cycle activities and increased to 9 people in cycle I, so if it is percentaged, the increase from pre-cycle to cycle is 50%. This is quite satisfying for the teacher because the children who have achieved the specified minimum score are 76. Significant changes also occur in cycle I to cycle II where the number of students who have completed cycle I activities is 9 students and rises to 23 students. in cycle II so that when percentaged the figure becomes 44%.